The Influence of Canva Application Features on The Graphic Design Confidence: A Case Study of College Students - Rahma, Desinta Nur; Ramadhani, Kayla Attya; Corazon, Marcella; Fami, Amata; Gloria Bagus, Irma Rasita (Politeknik Negeri Batam, 2024)
As technology evolves rapidly, opportunities for enhancing skills, such as graphic design, among college students continue to expand. Graphic design plays a crucial role in visually communicating ideas and messages. Canva, a popular graphic design platform, offers a user-friendly interface and diverse design templates, facilitating the creation of compelling graphics. This study aims to investigate the influence of the Canva application on the confidence levels of college students in their graphic design skills. Specifically, this research seeks to identify how Canva contributes to increasing students' confidence in creating graphic designs from the perspectives of interest, effectiveness, and time efficiency. Using a mixed-methods approach, the study employed both a questionnaire and interviews. The questionnaire, consisting of eight questions, collected responses from 67 participants. Additionally, in-depth interviews were conducted with 8 participants to gain further insights. The study finds that Canva significantly boosts graphic design confidence among college students. Its user-friendly interface and diverse templates enable easy creation of professional-quality designs, fostering creativity and skill development. This empowers students to feel more competent and self-assured in their design abilities, highlighting Canva's valuable role in education.